Peningkatan Literasi Lingkungan Siswa melalui Pembuatan Media Pembelajaran Herbarium Berbasis Proyek - Qurbaniah, Mahwar; Audina, Mia; Amri, Ahmad Faisal; Kurniawan, Arif Didik; Muldayanti, Nuri Dewi; Susilowati, Susilowati (Pakis Journal Institute, 2026)
This community service program aims to enhance students’ environmental literacy through the development of project-based herbarium learning media at SMP IT Az-Zahira Khatulistiwa. The problem identified in the partner school includes low levels of environmental literacy, limited use of contextual learning media, and the absence of structured project-based activities aligned with local biodiversity. The program employed the PDCA (Plan–Do–Check–Action) approach through need analysis, training, project implementation, and evaluation. Students and teachers participated in workshops on local plant identification, ethical specimen collection, drying techniques, and herbarium preparation. The project enabled students to explore their school environment, collect and classify plant specimens, and produce physical herbarium sheets as learning materials. The results showed a significant improvement in environmental literacy across knowledge, skills, and attitudes, with increases ranging from 35% to 58% based on pre- and post-test scores. The school also obtained a permanent herbarium collection as a contextual learning resource. Overall, the program strengthened students’ scientific skills, teachers’ capacity in project-based learning, and the school’s environmental literacy ecosystem.